On Corporate Tax Asymmetries and Neutrality - Paolo Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2000)
This article discusses the effects of corporate tax asymmetries under investment irreversibility. We introduce a tax scheme where the tax base is given by the firm's return net of a rate of relief. When the firm's return is less than the imputation rate, however, no tax refunds are allowed. Unlike symmetric tax systems, the scheme proposed is neutral with respect not only to income uncertainty but also to policy uncertainty.
Keywords: 330; Corporate taxation; irreversibility; neutrality; uncertainty